Forms of religiosity in selected works by Gertrud von le Fort - Piasta, Ewa Anna (Acta Universitatis Lodziensis. Folia Germanica, 2018)
Works by Gertrud von le Fort belong with literary religious discourse and enter a debate between Roman Catholicism and Protestantism.The writer sets her plots in the past, most frequently in the Middle Ages, which enables her to offer a critical assessment of contemporary political, ethical and religious issues.The article presents various connections between literature and religion, in terms of both motifs and style. References to religion are found in the thematic, axiological and linguistic layers of her texts. The analysed works comprise the novellas Der Dom (The Cathedral) and Am Tor des Himmels (At the Heavenly Gate) as well as the novel Magdeburgische Hochzeit (The Magdeburg Wedding). These works also reflect the phenomenon of the so-called cultural Christianity. Le Fort’s characters are not indifferent to the religious system, even if they do not fully identify with it.